Haikyu!! Volume 29, Found - Furudate, Haruichi, 1983- (Shonen Jump manga., 2018)
"Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? The game with Inarizaki heats up as Saeko Tanaka and her taiko drum crew arrive to cheer on Karasuno! The nation's best setter, Atsumu Miya, has even Nishinoya wincing when he's up to serve, and the Miya twins' version of the Freak Quick puts Hinata and Kageyama's to shame! Does Karasuno have any hope of beating this powerhouse and tournament favorite?!"--Page 4 of cover.